Pengendalian Proyektor LCD dari Jarak Jauh dengan Wifi dan Raspberry pi - Latif, Teguh Abdul; , Helman Muhammad, S.T., M.T (2017)
LCD Projector is always used in any learning process of FKI UMS's classes. Observation that has been done, thee tools always keep in the 'ON' mode even the class ends. On the other hand, FKI UMS provides Wi-Fi connection that can reach out every classroom in FKI UMS. This fact gives an idea about using Wi-Fi Connection to make LCD Projector remote controller. To bring that idea into reality, remote controller system that use Raspberry Pi as embedded controller and Wi-Fi UMS as communication infrastructure is created. The step starts with making the hardware and software programming, and the implementation follows after, after that, the program needs to be tested. Output of this research is a LCD Projector remote controller with responsive web page interfaces which can be accessed by the users by web-browser in the smartphone with a 100% success rate in 20 trials.